A Discovery of a Genetic Mutation Causing Reduction of Atrogin-1 Expression in Broiler Chicken Muscle - Li, Jinxiu; Hu, Yiqing; Li, Li; Wang, Yuzhe; Li, Qinghe; Feng, Chungang; Lan, He; Gu, Xiaorong; Zhao, Yiqiang; Larsson, Mårten; Hu, Xiaoxiang; Li, Ning (Frontiers in Genetics, 2019)
Chicken is bred all over the world and has significant economic value as one of the major agricultural animals. The growth rate of commercial broiler chicken is several times faster than its ancestor Red Jungle fowl. To further improve the meat production of commercial chicken, it is quite important to decipher the genetic mechanism of chicken growth traits. In this study, we found that broiler chicken exhibited lower level of E3 ubiquitin ligase muscle atrophy F-box (MAFbx or Atrogin-1) relative to its ancestor Red jungle fowls. As an ubiquitin ligase, Atrogin-1 plays a crucial role in muscle development in which its up-regulation often indicates the activation of muscle atrophic pathways. Here, we showed that the Atrogin-1 expression variance partly affect chicken muscle growth rate among different breeds. Furthermore, we demonstrated that the reduced expression of Atrogin-1 in broiler chicken was ascribed to a single nucleotide polymorphism (SNP), which inhibited the binding of transcription regulators and attenuated the enhancer activity. The decreased Atrogin-1 in broiler chicken would suppress the catabolism of muscle protein and preserve muscle mass. Our study facilitates the understanding of the molecular mechanism of chicken muscle development and carries a high translational impact to chicken breeding.